A recyclable self-supported nanoporous PdCu heterogeneous catalyst for aqueous Suzuki–Miyaura cross-coupling. Issue 88 (20th October 2021) - Du, Jialei; Xiang, Daili; Chen, Jie; Xia, Hehuan; Wang, Leichen; Liu, Fushan; Zhao, Yiwei; Zhang, Yuanyuan; Xu, Caixia; Wang, Bin
Abstract : A recyclable self-supported nanoporous PdCu alloy heterogeneous catalyst was developed for aqueous Suzuki–Miyaura cross-coupling. This catalyst could be easily separated from the product via centrifugation and reused several times. Abstract : Nanoporous PdCu (NP-PdCu) was prepared by the dealloying strategy from a PdCuAl ternary alloy precursor and characterized systematically using SEM, TEM, XRD, and XPS. NP-PdCu was demonstrated to be a competent self-supported heterogenous catalyst for Suzuki–Miyaura cross-coupling, affording a series of synthetically valuable biaryl compounds in good to excellent yields. This catalyst could be easily separated from the product via centrifugation and reused several times without obvious loss of catalytic performance.